PENGARUH KREATIVITAS DAN INOVASI WIDYAISWARA DALAM PENINGKATAN MUTU PEMBELAJARAN BAGI PESERTA DIKLAT - Zarkani (WIDYABORNEO, 2020)
This paper entitled The Influence of Creativity and Innovation of Widyaiswara in Learning Quality Improvement for Training and Education Participants, aims to determine the factors that influence creativity and innovation in improving the quality of learning, and knowing the steps that must be taken to improve the quality of learning and learning achievement for training participants. Supporting theory regarding the understanding of creativity and innovation, the characteristics of creative training participants, the nature of learning quality, the dominant factors in improving the quality of learning, and learning achievement.Factors that influence the creativity and innovation of training participants are internal and external factors. The internal factor is the nature of the human being itself which in itself is an impulse to develop and grow towards a business that is better than before, in accordance with the ability to think to fulfill all the needs that are needed. External factors include education participants' educational background, training that has been followed, organizational experience, level of welfare, and achievements. Efforts are made to improve the quality of learning and the achievements of training participants, through pre service education programs, in service education programs, and in service training programs.